(untitled) (Universal International Scientific Journal, 2026)
This article discusses the significance of integrating physics and chemistry in teaching Dalton’s and Avogadro‘s laws. The physical and chemical essence of these gas laws is elucidated, and the effectiveness of using interdisciplinary connections to explain them to students is substantiated. The paper also highlights how an integrated approach can foster students’ scientific thinking and logical reasoning skills.